Efeito de escalas temporais na definição de medidas de mitigação de impactos de rodovias - Costa, Aline Saturnino (2015)
The efficiency of mitigation measure are related to its place installation, which is determined by the distribution of roadkills on the highway varying with time and species. We evaluated the influence of the temporal pattern of roadkills in order to define the places for installation of mitigation measures, by identifying the seasonality of roadkills in differents vertebrates groups and the number of samples required to define the distribution of roadkills. The data were collected in 2002 and 2005 in southern Brazil and tests were performed at different groups: for all vertebrates together, every taxonomic class, some species and species groups. Using an autocorrelation function we found seasonality in roadkills of REPTILES, H. infrataeniatus and T. merianae in 2002 and VERTEBRATE, REPTILES and T. merianae in 2005. With a GAMM we found that minimum temperature the day before monitoring with the highest correlation to roadkill for each group. In order to define the number of samples needed to obtain the same pattern of distribution of roadkills obtained with annual sampling, we compared the density distribution of roadkills observed with the distribution obtained from a random sampling. BIRDS and species with seasonal roadkills require a high number of samples. Density distributions were similar to the annual roadkills with up 12 samples for other groups. To improve the effectiveness of mitigation measures is necessary to define the species to be mitigated, because groups are different with the variables related to roadkills and the number of samples needed. Thus, the number of samples must be defined according to the group of species evaluated, considering that even one year of samples may not be sufficient due to difference in density distributions among the roadkills in the years.